KAJIAN INTERTEKS DALAM MANUSKRIP TAFSIR JALÄ€LAYN KARANGASEM SEDAN REMBANG - Chilyatus Saadah (AL ITQAN: Jurnal Studi Al-Qur'an, 2019)
This research is a study of the Tafsīr Jalālayn Karangasem Sedan Manuscript, Rembang by focusing on ḥāshiyah contained in the manuscript. Kiai Syarbini, Karangasem believes that the Tafsīr Jalālayn Karangasem manuscript contains the Tafsīr Jalālayn text which contains interpretations from surah al-Fatihah to surah al-Kahfi. In this manuscript there is additional information that contains an explanation of the words in the Qur’an and words in the Tafsīr Jalālain. By using the theory of intertext, this study seeks to search for and find what books are used as references in writing of ḥāshiyah contained in manuscript Tafsīr Jalālain Kiai Syarbini Karangasem. In intertext theory, a text cannot be alone. The appearance of the text is caused by the help of other texts. This research succeeded in identifying the books used as a reference source in the ḥāshiyahTafsīr Jalālayn manuscript, which include: Tafsir al-Bayḍāwī, Tafsir al-Qurṭūbi, Tafsīr al- Ṣhāwī, and Tafsir Mafātiḥ al-Ghayb.The findings of this manuscript are indicative of the existence of Tafsīr learning as well as efforts to provide comments on earlier interpretations than previously thought, at least in the 19th century Rembang area which is said to have experienced a learning emptiness of tafsir books.